2018
DOI: 10.1007/s11886-018-1015-6
|View full text |Cite
|
Sign up to set email alerts
|

Resynchronization Therapy for Patients with Congenital Heart Disease: Are We Ready for Prime Time?

Abstract: CRT is a valuable tool in the treatment of heart failure in the setting of CHD. Current evidence points toward the ability of this therapy to increase hemodynamic parameters and reduce heart failure-related symptoms. Within the CHD population, patients with systemic left ventricles appear to benefit the most from CRT. Utilization of CRT in CHD has been technically difficult due to the complexity and variety of anatomic substrates. However, lateral thoracotomies and other advances have made implantation more fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…In contrast, a lateral thoracotomy may provide surgeons with access to pristine tissue. Finally, CRT devices are not MRI compatible, which limits later imaging options in the long‐term management of younger patients …”
Section: End‐stage Congenital Heart Disease—the Next Big Challengementioning
confidence: 99%
“…In contrast, a lateral thoracotomy may provide surgeons with access to pristine tissue. Finally, CRT devices are not MRI compatible, which limits later imaging options in the long‐term management of younger patients …”
Section: End‐stage Congenital Heart Disease—the Next Big Challengementioning
confidence: 99%
“…A retrospective review on 20 patients with congenitally corrected transposition of the great arteries reported that CRT implantation is feasible, and that the long-term outcome is favorable but linked to systematic morphologic RV dysfunction in some patients [42]. Since most of the studies available are retrospective in nature, the impact of CRT on long-term prognosis in this population is still unknown [43, 44]. …”
Section: Concomitant Cardiac Conditionsmentioning
confidence: 99%